Granulocyte colony-stimulating factor in traumatic spinal cord injury. Issue 7 (July 2021) - Aschauer-Wallner, Stephanie; Leis, Stefan; Bogdahn, Ulrich; Johannesen, Siw; Couillard-Despres, Sebastien; Aigner, Ludwig
Highlights: G-CSF exerts activities in the central nervous system. G-CSF has strong anti-inflammatory activities in acute and chronic CNS lesion. G-CSF - counteracting secondary damage after traumatic SCI. G-CSF improves functional outcome in patients with traumatic SCI. G-CSF - a safe and effective drug for the treatment of acute and chronic tSCI. Abstract: Granulocyte colony-stimulating factor (G-CSF) is a cytokine used in pharmaceutical preparations for the treatment of chemotherapy-induced neutropenia. Evidence from experimental studies indicates that G-CSF exerts relevant activities in the central nervous system (CNS) in particular after lesions. In acute, subacute, and chronic CNS lesions, G-CSF appears to have strong anti-inflammatory, antiapoptotic, antioxidative, myelin-protective, and axon-regenerative activities. Additional effects result in the stimulation of angiogenesis and neurogenesis as well as in bone marrow stem cell mobilization to the CNS. There are emerging preclinical and clinical data indicating that G-CSF is a safe and effective drug for the treatment of acute and chronic traumatic spinal cord injury (tSCI), which we summarize in this review.